Organizational Readiness to Implement Community Pharmacy-Based Opioid Counseling and Naloxone Services: A Scoping Review of Current Practice Models and Opportunities - Lindsey Hohmann; Klaudia Harris; Yi Zhao; Karen Marlowe; Haley Phillippe; Chris Correia; Brent Fox (MDPI AG, 2023)
The purpose of this study was to explore existing practice models and opportunities surrounding community pharmacist-delivered opioid counseling and naloxone (OCN) services in the U.S., with the goal of enhancing organizational readiness and improving patient access. A scoping literature review was conducted. English-language articles published in peer-reviewed journals from January 2012-July 2022 were sought via PubMed, CINAHL, IPA, and Google Scholar using permutations of terms such as "pharmacist/pharmacy", "opioid/opiate", "naloxone", "counseling", and "implement/implementation". Original articles reporting the resources/inputs (personnel; pharmacist full-time equivalents; facilities and expenses; in-house versus outsourced personnel), implementation processes (legal source of pharmacist authority; patient identification strategies; intervention procedures; workflow strategies; business operations), and programmatic outcomes (uptake and delivery; interventions made; economic impact; patient or provider satisfaction) of pharmacist-delivered OCN services in community (retail) settings were retained. Twelve articles describing ten unique studies were included. The studies primarily used quasi-experimental designs and were published from 2017 to 2021. The articles described seven broad program elements/themes: interprofessional collaboration (n = 2); patient education format including one-on-one patient education (n = 12) and group education sessions (n = 1); non-pharmacist provider education (n = 2); pharmacy staff education (n = 8); opioid misuse screening tools (n = 7); naloxone recommendation/dispensing (n = 12); and opioid therapy and pain management (n = 1). Pharmacists screened/counseled 11-2716 patients and provided 11-430 doses of naloxone. Limited implementation costs, patient/provider satisfaction, or economic impact measures were reported. This review may serve as a guide for community pharmacists in implementing OCN services in their own practices. Future studies should clarify OCN program implementation costs, patient/provider satisfaction, and the economic impact.